Analisis Kepuasan Pengguna Aplikasi Renshuu dalam Pembelajaran Bahasa Jepang Menggunakan Metode UEQ - Rasendriya, Achmad Syahmi; Halimi, Keysha Maulina; Salsabila, Alya Putri; Aji, Wahyu Mustika; Lestari, Humannisa Rubina (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This study examines user satisfaction with the Renshuu application for Japanese language learning using the User Experience Questionnaire (UEQ) method. The research aims to evaluate user experience aspects, including support, ease of use, efficiency, clarity, excitement, interest, innovation, and modernity. Data were collected by 25 active Renshuu users. Quantitative analysis revealed average scores across all UEQ dimensions in the